A polyetheylene-lined bioreactor system for plant cell and hairy root culture of hyoscyamus muticus - Bacani, Florinda T. (Animo Repository, 2001)
The growth of plant cultures (Hyoscyamus muticus) was demonstrated in a fabricated prototype large-scale bioreactor system. The system vessel, lined with a 6-mil thick polyethylene polymer, was operated as a gas-sparged airlift bioreactor. The bottom of the tank was contoured with an asymmetric V-shaped baffle for adequate mixing and sufficient oxygen mass transfer. A volumetric oxygen mass transfer (KLa) value of 15.2 h-1 at 0.25 volumes of gas per volume of media per minute (vvm) and an average mixing time (tm) of 4.5 to 9 minutes were achieved. Growth and biomass accumulation were estimated through refractive index as an indicator of sugar levels and electrical conductivity as an indicator of inorganic nutrients. A linear relationship was obtained between fresh weight and fry weight cell density and medium conductivity change and refractive index change. After 13 days of batch culture, the 40-I polyethylene-lined batch reactor (28.5-I working volume, w.v.) contained cells with a biomass of 2.9-kg fresh weight (FW) or 199 g dry weight (DW), which is equivalent to an accumulated DW density of 9.46 g/l. The growth of the culture achieved a sustained effective specific growth rate of 0.26 day-1. The growth performance of cell culture in this reactor was found to be comparable to that (1) in 9-I prototype bioreactor and (2) in a modified stirred-tank bioreactor (STR). Both Fluorescein Diacetate (FDA) and Triphenyl Tetrazolium Chloride (TTC) methods assessed the healthy condition and proved that there were no evidences of cell damage or breakage during the operation of the polyethylene-lined bioreactor run. Sterilization of the polyethylene-lined bioreactor was done by gas-phase sterilization using an ethylene oxide: carbon dioxide (EtO:CO2). Experimental measurements and modeling of EtO diffusion were obtained to characterize the EtO:CO2 sterilization scheme. Diffusion coefficients of 0.9 x 10-7 cm2/sec and 2.1 x 10-7 cm2/sec demonstrated that only less than an hour of aeration is needed for sterilant desorption. The test for the presence of sesquiterpenes secondary metabolites in the prototype polyethylene-lined bioreactor was done by fungal elicitation techniques using high performance liquid chromatography (HPLC). The HPLC chromatogram was further identified by Gas Chromatography (GC), Mass Spectrometry (MS), Ultraviolet-Visible (UV) spectroscopy), and Nuclear Magnetic Resonance (NMR) spectroscopy.